2008
DOI: 10.1021/jp8005469
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Uptake of N2O5on Aqueous H2SO4Solutions Coated with 1-Component and 2-Component Monolayers

Abstract: Reactive uptake of N(2)O(5) on aqueous sulfuric acid solutions was studied in the presence of 1-component (octadecanol) and 2-component (octadecanol + phytanic acid) monolayers. In the 1-component monolayer experiments, the reactive uptake coefficient depended strongly on the molecular surface area of the surfactant. Also, the 1-component monolayer showed significant resistance to mass transfer even when the fractional surface coverage of the surfactant was less than 1. For example, a monolayer of 1-octadecano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 87 publications
6
82
0
Order By: Relevance
“…Obviously, the hydrolysis of the much less soluble N 2 O 5 may already be affected by less densely packed organic coatings, but might also be more sensitive to the water activity of the mixed aqueous particles. In the most recent study, Cosman et al (2008) found effects that are related to what we have observed for HNO 3 in that a monolayer of octadecanol was strongly inhibiting the uptake of N 2 O 5 , while the addition of a branched surfactant strongly decreased the resistance to N 2 O 5 uptake again.…”
Section: Discussion Of Effects Of Fatty Acid Coatingssupporting
confidence: 71%
See 1 more Smart Citation
“…Obviously, the hydrolysis of the much less soluble N 2 O 5 may already be affected by less densely packed organic coatings, but might also be more sensitive to the water activity of the mixed aqueous particles. In the most recent study, Cosman et al (2008) found effects that are related to what we have observed for HNO 3 in that a monolayer of octadecanol was strongly inhibiting the uptake of N 2 O 5 , while the addition of a branched surfactant strongly decreased the resistance to N 2 O 5 uptake again.…”
Section: Discussion Of Effects Of Fatty Acid Coatingssupporting
confidence: 71%
“…A number of recent studies have addressed the effects of organic coatings on the phase transfer of atmospherically relevant molecules (Däumer et al, 1992;Jefferson et al, 1997;Folkers et al, 2003;Thornton and Abbatt, 2005;Glass et al, 2006;Gilman and Vaida, 2006;McNeill et al, 2006;Park et al, 2007;Clifford et al, 2007;Cosman et al, 2008). The observed effects different surfactants have vary substantially and depend on the substrate, the monolayer properties and also on the type of trace gas and its sink process in the condensed phase.…”
Section: Introductionmentioning
confidence: 99%
“…48 The presence of organic coatings on aqueous aerosols can suppress heterogeneous N 2 O 5 hydrolysis by providing a barrier through which N 2 O 5 needs to diffuse in order to undergo hydrolysis. [49][50][51] Reactive uptake of O 3 and NH 3 to organic aerosols exhibits a pronounced decrease as RH decreases owing to the phase transformation from viscous liquid to semi-solid or amorphous solid. 16,52 Therefore, the presence of a semi-solid matrix may effectively shield reactive organic compounds from chemical degradation in long-range transport.…”
Section: Heterogeneous and Multiphase Chemistrymentioning
confidence: 99%
“…The heterogeneous loss rate of N 2 O 5 is a function of the total aerosol surface area and of the fraction of gas-particle collisions resulting in N 2 O 5 uptake. The latter is aerosol composition dependent, enhanced at higher aerosol water content (e.g., Hu and Abbatt, 1997;Hallquist et al, 2003;Thornton et al, 2003), reduced in the presence of organic coatings (e.g., Cosman and Bertram, 2008;McNeill et al, 2006), and inversely proportional to NO − 3 (e.g., Wahner et al, 1998;Hallquist et al, 2003;Bertram and Thornton, 2009;Wagner et al, 2013).…”
Section: Chemistry In the Dynamic Near-surface Atmospherementioning
confidence: 99%